Sitz bath for hemoroidectomy pain relief - Sari, Rika Cahya Endah; Handayani, Estrin; Wahyuningtyas, Eka Sakti; Chisupa, Eric (Universitas Muhammadiyah Magelang, 2022)
Hemorrhoids are diseases affecting the rectum and anus caused by damage to the hemorrhoidal plexus or blood vessels around the rectum and anus. If hemorrhoids are large lumps, then one of the steps is hemorrhoid surgery. One of the effects of post-hemorrhoidectomy is pain felt in post-hemorrhoidectomy patients. This study aims to apply the application of sitz bath hydrotherapy to decrease pain intensity in post-hemorrhoidectomy patients. The method used for this application is a case study. The length of pain felt was measured using the VAS and NRS pain scales. The results of this study indicate that the application of sitz bath hydrotherapy with the main ingredient of warm water at a temperature of 40-45OC can be applied to post-hemorrhoidectomy patients who experience moderate to severe pain. Keywords: Nursing care; pain management; surgery; complementary therapy; nursing intervention